The impact of manual patient handling on work ability: A cross-sectional study in a Brazilian hospital - Bernardes, João Marcos [UNESP] (2022)
Aim: To investigate the level of self-reported work ability and its association with manual patient handling in healthcare workers. Design: Cross-sectional study adhering to the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines. Methods: A total of 320 healthcare workers answered a self-administered questionnaire regarding manual patient handling, work ability, occupational factors, occurrence of low back pain and sociodemographic and lifestyle factors from November 2016 to March 2017. The association between manual patient handling and low back pain was analysed with Poisson regression models. Results: The prevalence ratio of inadequate work ability was 43.42%. Manual patient handling (PR 1.375, 95% CI 1.038–1.821), bachelor education (PR 2.150, 95% CI 1.272–3.632), less than bachelor education (PR 2.166, 95% CI 1.218–3.855), seniority (PR 1.049, 95% CI 1.024–1.086), poor sleep quality (PR 1.425, 95% CI 1.13–1.796) and presence of low back pain (PR 2.003, 95% CI 1.314–3.052) were all positively associated with an inadequate work ability.